ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI REPURCHASE INTENTION PADA PT INDOMARCO PRISMATAMA (INDOMARET) - Wasiman, Wasiman; Wangdra, Yvonne; Wibowo, Agung Edy; Wangdra, Suvianto (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
This study set out to determine if hedonic values and utilitarian values both had an effect on consumer satisfaction. 3) To examine the relationship between hedonic and utilitarian values and consumer happiness. 4) To determine how utilitarian and hedonistic values affect consumer satisfaction. The quantitative descriptive techniques used in this investigation. the procedure of collecting data via a questionnaire. The population of the research consisted of clients of PT Indomarco Prismatama (Indomaret) in Batam. The Slovin formula sampling method was used to choose up to 423 respondents. The research's conclusions are as follows: With a significance threshold of less than 0.05, the t test variable utilitarian value (X1) on customer happiness (Y) provided a value of 5.905 that was higher than the t table (5.905 > 1.9719). (0 . 000 0.05). The value of t arithmetic, which is more than t table (136.479 > 1.9719), is 136.479 in the hedonic variable value (X2) to Repurchase Intention with a significance of less than 0.05 (0.000 0.05). (Y). the multiple linear regression formula, Y = (-1.351) + 0.413 (X1) + 0.674 (X2) + e The study's findings suggest that hedonic and utilitarian value determinants have an impact on PT Indomarco Prismatama (Indomaret) consumers in Batam.